Comparison of fucosylated chondroitin sulfate structure from three holothurian species in Sabah, Malaysia - Pang, Myron Jyan Yu (2016)
Fucosylated chondroitin sulfate (FuCS) is a unique compound from commercially important holothurians that possess pharmaceutical bioprospect through its many physicochemical activities but was not explored in non-targeted species of Stichopus horrens, Holothuria atra and Holothuria arenicola. This study has examined the levels and structure of FuCS in these three holothurian species of Sabah using combination of spectrometry, spectroscopy and chemometrics techniques. Through extraction and purification, the FuCS levels for H. arenicola was 66.24±0.307 μg/ml, H. atra was 73.16±0.293 μg/ml and S. horrens was 104.47±0.338 μg/ml. High performance liquid chromatography analysis confirmed each of the extracts had approximately equimolar of 0-glucuronic acid (GlcUA) and D-N-acetylgalactosamine (GalNAc), resembling chondroitin sulfate analogs. Stichopus horrens had significant higher fucose ratio at 0. 78 per mol GalNAc followed by H. atra at 0.45 per mol GalNAc and H. arenicola at 0.44 per mol GalNAc. Liquid chromatography quadrupole time-of-flight mass spectrometry (LCQTOF/MS) analysis had deduced the mode of mass breakage of the FuCS components and determined the extracts purity of >96.1 %. Gas chromatography mass spectrometry (GCMS) analysis suggested sulfation was on the fourth and sixth carbon of acetylgalactosamine. Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) analysis showed additional evidence of sulfate and sulfation positions on the compound. The second derivatives IR spectra of each holothurian species had distinct absorptions difference in the region 860-800 cm-1 , indicating the sulfation position from each species was different. Principal component analysis (PCA) models had facilitated the IR discrimination and found the greatest influential variables were from carbonyl region, seconded by sulfation region and to a lesser extend of ring vibration region. Both PCA models and hierarchical clustering analysis (HCA) clustered the samples precisely to three clusters. The HCA analysis showed low degree of heterogeneity among the sample branches while samples from S. horrens forming an isolated branch at distance height of 285.234 using classical PCA scores and 0.057 using robust PCA scores. In conclusion, these three previously unexplored holothurian species had been proven to possess analogous FuCS chemical structure from commercially important species counterparts.